Cytokine profile in cases with premature elevation of progesterone serum concentrations during ovarian stimulation - Nikolettos, N; Asimakopoulos, B; Köster, F; Schöpper, B; Schulz, Ch; Caglar, G. S; Efthimiadou, A; Pagonopoulou, O; Diedrich, K; Al-Hasani, S (Physiological research, 2008)
The aim of this study was to investigate the concentrations of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), leptin, tumor necrosis factor-alpha, interleukin (IL)-1beta and IL-6, in cycles with a premature rise of serum progesterone. 25 intracytoplasmic sperm injection (ICSI) cycles with (Group 1) and 25 ICSI cycles without a premature progesterone elevation (Group 2) were included. The cut-off value of serum progesterone on the day of human chorionic gonadotropin (hCG) administration was 0.9 ng/ml. The indication for ICSI was male factor infertility exclusively. On the day of hCG injection, serum IL-6, VEGF and bFGF were significantly higher in Group 1 (7.7+/-24.5 pg/ml, 290.2+/-161.4 pg/ml and 15.7+/-8.2 ng/ml respectively) than in Group 2 (1.7+/-0.7 pg/ml, 175.2+/-92.1 pg/ml, and 9+/-1.6 ng/ml respectively). On the day of follicular puncture, serum cytokine concentrations were similar in the two groups. IL-6 intrafollicular concentrations were higher in Group 1 (14.7+/-20.7 pg/ml) than in Group 2 (9+/-9.3 pg/ml, p=0.031). There were no differences regarding the ICSI outcome. Patients with serum progesterone above 0.9 ng/ml, have elevated serum concentrations of IL-6, VEGF, and bFGF, as well as elevated intrafollicular concentrations of IL-6. The outcome of ICSI cycles is not associated with premature elevation of progesterone when the cut-off value is set at 0.9 ng/ml.
Keywords: fibroblastový růstový faktor 2; Ovulation Induction; leptin; menstruační cyklus; Analysis of Variance; Progesterone; Tumor Necrosis Factor-alpha; Menstrual Cycle; cytokiny; folikulární tekutina; Interleukin-6; Adult; Case-Control Studies; dospělí; interleukin-1beta; Sperm Injections, Intracytoplasmic; referenční hodnoty; Time Factors; Estradiol; Reference Values; lidé; ženské pohlaví; studie případů a kontrol; analýza rozptylu; interleukin-6; Humans; progesteron; intracytoplazmatické injekce spermie; indukce ovulace; testosteron; časové faktory; Interleukin-1beta; TNF-alfa; vaskulární endoteliální růstový faktor A; Cytokines; Follicular Fluid; Vascular Endothelial Growth Factor A; Fibroblast Growth Factor 2; Female; Testosterone; Leptin; estradiol